Perlindungan Hukum Mitra Ojek Daring di Indonesia - Mawanda, M Kharis; Muhshi, Adam (Lentera Hukum, 2019)
As one of the countries with the highest population density in the world, the opportunity to work in Indonesia is not directly proportional to its population density so that the number of unemployed is still relatively high. The development of technology has entered in business and it is seen as an alternative with its emergence of the online transportation service providers such as Go-Jek. In the case of partnership agreements used by partners with Go-Jek, partners as parties that have weak bargaining power while Go-Jek has strong bargaining power. From a legal standpoint, the main problem is the absence of legislation that clearly regulates online motorcycle taxis and partnership agreements between partners and Go-Jek. Therefore, it is necessary to analyze the online motorcycle taxi, and the legal protection aspects against partners based on partnership agreements and legal remedies in the event of a dispute in the implementation of the partnership agreement. With doctrinal research, this article argues that the partnership agreement is an agreement on innominaat so that in its implementation it should not conflict with the laws and regulations on it. The results of the study indicate that online motorcycle taxis have not yet been regulated in Indonesian laws and regulations, the partnership agreement has not provided legal protection for partners and in the event of a dispute, there can be legal action in accordance with the partnership agreement clause. Keywords: Legal Protection, Partnership Agreement, Online Taxi.